1989
DOI: 10.1093/ajcp/91.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Auto Anti-M: Clinical and Serologic Findings of Seven Patients from One Hospital and Review of the Literature

Abstract: Auto-anti-M antibodies are not commonly documented serologically. A review of the literature reveals only ten cases with no consistent clinical or laboratory findings. In their institution, over a 12-year period, the authors have identified this autoantibody in seven patients, suggesting that it may not be such a rare entity but rather may be underdiagnosed. In this article the authors describe the pertinent clinical and serologic findings in their seven patients, as well as review the salient features of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1989
1989
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In fact, in this study, the average age of patients studied with auto‐anti‐M was 73 years old while the average age of patients with allo‐anti‐M/N was 51 years old. Nevertheless, the incidence of auto‐anti‐M is low with one case series of seven patients with auto‐anti‐M reported in the literature by Sacher et al 21 In this case series, the patients had a variety of clinical features and diagnoses for which one could not identify a common cause accounting for the development of an auto‐anti‐M 21 …”
Section: Discussionmentioning
confidence: 90%
“…In fact, in this study, the average age of patients studied with auto‐anti‐M was 73 years old while the average age of patients with allo‐anti‐M/N was 51 years old. Nevertheless, the incidence of auto‐anti‐M is low with one case series of seven patients with auto‐anti‐M reported in the literature by Sacher et al 21 In this case series, the patients had a variety of clinical features and diagnoses for which one could not identify a common cause accounting for the development of an auto‐anti‐M 21 …”
Section: Discussionmentioning
confidence: 90%
“…At least 15 cases of patients with autoanti-M have been reported and reviewed by Sacher et al . [ 11 ] According to him, 11 were non significant while rest four gave some symptoms of cold hemagglutinin disease. Anti–M may show a dosage effect as in the case of the female patient, reacting more strongly with homozygous cells (M+N-) than cells (M+N+).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in contrast to our finding from the whole blood donor, where the anti-M was reactive at room temperature with optimum activity at 4°C. Sacher et al 12 described 17 cases of autoanti-M, of which four had symptoms of cold agglutinin disease, such as Raynaud's phenomenon, livedo reticularis, and acrocyanosis, and two had mild hemolysis; the rest were asymptomatic despite having a significant titer of the autoanti-M. Patients with anti-M have been described by Tandon et al 13 and Kaur et al 14 These antibodies were identified as IgM, causing ABO grouping discrepancy, with optimum reactivity below 37°C.…”
Section: Discussionmentioning
confidence: 99%